The Role Of Digital Platforms In Enhancing Customer Engagement And Business Performance In The Digital Economy - Riris Hutapea; Ezra Reni Silva Situmorang; Daniel Pangaribuan; Efraim Prasetyo Siahaan (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2024)
The rapid development of the digital economy has significantly transformed how businesses operate, interact with customers, and create value. Digital platforms such as online marketplaces, social media, and business applications play a critical role in supporting marketing activities, communication processes, and customer relationship management. This study aims to analyze the role of digital platforms in enhancing customer engagement and business performance within the digital economy. The research employs a literature review approach by examining relevant scholarly articles published between 2020 and 2023. The findings indicate that digital platforms can enhance customer engagement through more interactive communication, personalized services, and increased customer participation within digital ecosystems. Improved customer engagement subsequently contributes to better business performance, including increased sales, stronger customer loyalty, and enhanced product and service innovation. However, the adoption of digital platforms also presents several challenges, including digital capability gaps, data security concerns, and dependence on platform ecosystems. Therefore, businesses need to develop integrated digital strategies and adopt customer-centric approaches to maximize the benefits of digital platforms in improving business performance.